Ambivalence in distinguishing double burden of malnutrition among school children in three districts of south India - Chandana Hombaiah; Anil S. Bilimale; B. Madhu; M.R. Narayana Murthy (Elsevier, 2021)
Objectives: To assess the nutritional status of school-going children in the age group 6-17 years and to compare BMI growth percentile charts of WHO and IAP (Indian Academy of Paediatrics). Methods: A cross-sectional study was conducted among school children aged 6-17 years studying in 44 schools of three districts in South India, between 2018 and 2019. A total of 8688 students were assessed for their height and weight. Anthropometric data were plotted on both WHO and IAP BMI charts. Results: There were 50.1% boys and 49.9% girls; 32.1% were urban and 67.9% from rural localities. According to the WHO BMI chart, 14.7% of the school students were severely thin, 15.8% were thin, 6.9% were overweight and 2.2% were obese. Under-nutrition among boys was 9.7% more prevalent than girls. Overweight prevalence was higher in girls (9.6%); 4.1% higher prevalence among urban than rural girls. The difference between the two BMI chart measurements for <3rd percentile possessed a variation of 24.2% for boys and 12.3% for girls. Significant undernutrition (53.6%) was among 6-8yrs and overnutrition (11%) among adolescents. Conclusion: The study reveals a double burden of malnutrition with gender, age, and geographic disparity. Boys were severely thin than girls while girls were overweight than boys. Rural students were underweight whereas urban students were overweight and obese. Thinness was inversely proportional to age. The sensitivity to determine under-nutrition was with the WHO chart whilst the IAP chart was for over-nutrition.